Artificial Intelligence And Its Effect On Labor Market-with Reference To The Area Of Middle East And North Africa- - Ibtissem Alliouche Kerboua (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Through this research paper, we will try to identify artificial intelligence and its effect on labor market with reference to the Middle East and North Africa region, and the main objective of the research is to identify How AI and its applications will impact the labor market, whether negatively or positively, in light of the major changes that occurred at the global level, most notably the COVID-19 pandemic and the digital transformation that has become inevitable. Based on the statistics and studies provided, the study reached that the impact of AI on the labor market is complicated and multifaceted, with both opportunities and challenges. It underscores the importance of proactive strategies to manage transitions, promote inclusive growth, and ensure that the benefits of AI are shared widely across society.